2013
DOI: 10.1121/1.4794366
|View full text |Cite
|
Sign up to set email alerts
|

The time course of perception of coarticulation

Abstract: The perception of coarticulated speech as it unfolds over time was investigated by monitoring eye movements of participants as they listened to words with oral vowels or with late or early onset of anticipatory vowel nasalization. When listeners heard [CṼNC] and had visual choices of images of CVNC (e.g., send) and CVC (said) words, they fixated more quickly and more often on the CVNC image when onset of nasalization began early in the vowel compared to when the coarticulatory information occurred later. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
104
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 53 publications
13
104
2
Order By: Relevance
“…As we discussed earlier, listeners are sensitive both to the appropriateness of coarticulatory cues for an upcoming sound (Dahan et al, 2001;Dahan & Tanenhaus, 2004;Gow & McMurray, 2007), as well as to the specific timing of when coarticulatory cues become available in the speech signal (Beddor et al, 2013;Salverda et al, 2014). For instance, Beddor et al (2013) showed that listeners' fixations converged on a CVNC word (e.g., bent) more quickly when nasalization started early in the vowel than when it started late in the vowel.…”
Section: Glottalization As Coarticulationmentioning
confidence: 99%
See 3 more Smart Citations
“…As we discussed earlier, listeners are sensitive both to the appropriateness of coarticulatory cues for an upcoming sound (Dahan et al, 2001;Dahan & Tanenhaus, 2004;Gow & McMurray, 2007), as well as to the specific timing of when coarticulatory cues become available in the speech signal (Beddor et al, 2013;Salverda et al, 2014). For instance, Beddor et al (2013) showed that listeners' fixations converged on a CVNC word (e.g., bent) more quickly when nasalization started early in the vowel than when it started late in the vowel.…”
Section: Glottalization As Coarticulationmentioning
confidence: 99%
“…We were interested in looking at two measures, following Beddor et al (2013). The first was the latency of the first correct fixation to the target word.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of work has focused on the individual differences in the perception of the acoustic cues that define sound contrasts, and shown that this relation may vary as a function of factors such as language background (Escudero & Boersma, 2004;Schertz, Cho, Lotto, & Warner, 2015), cue weighting strategy (Beddor, McGowan, Boland, Coetzee, & Brasher, 2013;Kong & Edwards, 2011), as well as cognitive abilities (e.g. attention: Janse & Adank, 2012; working memory: Francis & Nusbaum, 2009; cognitive processing style: Stewart & Ota, 2008;Yu, 2010).…”
Section: Introductionmentioning
confidence: 99%